Changes in peripheral refractive profile after orthokeratology for different degrees of myopia - González-Méijome, José Manuel (2016)
Purpose: The purpose of this study was to evaluate the effect of orthokeratology for different degrees of myopia correction in the relative location of tangential (FT) and sagittal (FS) power errors across the central 70 of the visual field in the horizontal meridian. Methods: Thirty-four right eyes of 34 patients with a mean age of 25.2 ± 6.4 years were fitted with Paragon CRT (Mesa, AZ) rigid gas permeable contact lenses to treat myopia (2.15 ± 1.26D, range: 0.88 to 5.25D). Axial and peripheral refraction were measured along the central 70 of the horizontal visual field with the Grand Seiko WAM5500 open-field auto-refractor. Spherical equivalent (M), as well as tangential (FT) and sagittal power errors (FS) were obtained. Analysis was stratified in three groups according to baseline spherical equivalent: Group 1 [MBaseline = 0.88 to 1.50D; n = 11], Group 2 [MBaseline = 1.51 to 2.49D; n = 11], and Group 3 [MBaseline = 2.50 to 5.25D; n = 12]. Results: Spherical equivalent was significantly more myopic after treatment beyond the central 40 of the visual field (p50.001). FT became significantly more myopic for all groups in the nasal and temporal retina with 25 (p 0.017), 30 (p 0.007) and 35 (p 0.004) of eye rotation. Myopic change in FS was less consistent, achieving only statistical significance for all groups at 35 in the nasal and temporal retina (p 0.045). Conclusions: Orthokeratology changes significantly FT in the myopic direction beyond the central 40 of the visual field for all degrees of myopia. Changes induced by orthokeratology in relative peripheral M, FT and FS with 35 of eye rotation were significantly correlated with axial myopia at baseline. Keywords: Field